Photocatalytic metallic nanomaterials immobilised onto porous structures: Future perspectives for at-source pharmaceutical removal from hospital wastewater and potential benefits over existing technologies. (April 2023) - Valdivia, Manuel-Thomas; Taggart, Mark A.; Pap, Sabolc; Kean, Alistair; Pfleger, Sharon; Megson, Ian L.
Abstract: Active pharmaceutical ingredients (APIs) are continuously released via hospital effluents and have been shown to be toxic to aquatic organisms, even at very low concentrations. Future risks to human health might also emerge due to accumulation of these compounds in food chains, through contamination of water supplies and propagation of antimicrobial resistance (AMR). The ongoing global rise in drug prescribing rates is increasing API concentrations in aquatic environments. Current wastewater treatment plants (WWTPs) are ineffective at removing many of these compounds. Pilot-scale advanced oxidation processes (AOPs) at WWTPs, such as UV-irradiation or ozone, are not considered sustainable at the industrial scale, due to their high operating cost and the potential for formation of toxic by-products. By contrast, photocatalytic AOPs only require light-induced activation of a reusable photocatalyst to eliminate the most persistent APIs. Despite their sustainable characteristics, photocatalytic AOPs have rarely been assessed for suitability in flow environments, such as hospital wastewater. This review highlights the advantages of photocatalytic AOP based wastewater treatment compared to existing AOPs. It also explores the immobilisation of effective photocatalytic metallic nanomaterials onto carbon-based porous support structures as a future-proof treatment concept for the elimination of APIs from hospital wastewater. Graphical abstract: Unlabelled Image Highlights: Low concentrations of drugs in hospital wastewater can cause ecotoxic effects. Hospitals are key point-sources for active pharmaceutical ingredients (APIs). Conventional wastewater treatment ineffectively removes persistent APIs. Advanced oxidation can remove many APIs but is expensive or forms toxic by-products. Immobilised photocatalysis can sustainably eliminate APIs from hospital wastewater.